University Libraries in Pakistan - Muhammad Zulqarnain Akhtar (Türk Kütüphaneciliği)
The paper aims to examine the development and growth of the university libraries in Pakistan. It also examines the obstacles in the provision of better library services in the universities of the country. The study is based on an exten- sive review of the available literature, personal observations of the author and discussions with the senior library professionals. It was found that the situation of university libraries in Pakistan is a satisfactory compared to other types of libraries, but they are not meeting the required standards and are not participat- ing in the universities' educational and research programs satisfactorily.